2019
DOI: 10.1111/jvim.15663
|View full text |Cite
|
Sign up to set email alerts
|

A major facilitator superfamily domain 8 frameshift variant in a cat with suspected neuronal ceroid lipofuscinosis

Abstract: A 2-year-old male domestic shorthair cat was presented for a progressive history of abnormal posture, behavior, and mentation. Menace response was absent bilaterally, and generalized tremors were identified on neurological examination. A neuroanatomical diagnosis of diffuse brain dysfunction was made. A neurodegenerative disorder was suspected. Magnetic resonance imaging findings further supported the clinical suspicion. Whole-genome sequencing of the affected cat with filtering of variants against a database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These previous studies illustrate the limitations of sequencing individual candidate genes compared to WGS/WES approaches for identification of disease-associated variants. The only other pathogenic variants responsible for feline NCL were identified in MFSD8 of a domestic shorthaired cat using WGS ( Guevar et al 2019 ). MFSD8 variants underlie the CLN7 form of NCL in human subjects ( Mole et al 2011 ) and dogs ( Katz et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These previous studies illustrate the limitations of sequencing individual candidate genes compared to WGS/WES approaches for identification of disease-associated variants. The only other pathogenic variants responsible for feline NCL were identified in MFSD8 of a domestic shorthaired cat using WGS ( Guevar et al 2019 ). MFSD8 variants underlie the CLN7 form of NCL in human subjects ( Mole et al 2011 ) and dogs ( Katz et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence variants that cause NCL in sheep have also been identified in the ovine orthologs of three of the CLN genes ( Tyynela et al 2000 ; Tammen et al 2006 ; Frugier et al 2008 ). Although a number of cases of NCL have been reported in cats based on disease phenotype ( Nakayama et al 1993 ; Bildfell et al 1995 ; Kuwamura et al 2009 ; Chalkley et al 2014 ), only one feline NCL-causing variant has been identified (a frameshift in MFSD8 associated with CLN7 disease) ( Guevar et al 2019 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The age of onset of the disease in the case described herein and possibly the dam was between 2 and 3 years of age. There were similarities with regard to the clinical course of NCL in other species such as cognitive changes and vision loss in humans (Schulz et al., 2013) or blindness, pacing, anxiety, disorientation and ataxia in other animal species (Ashwini et al., 2016; Guevar et al., 2020; Guo et al., 2015; McBride et al., 2018). In rabbits, to the best of our knowledge, a similar combination of clinical signs has only been described in a miniature lop pet rabbit with GM2 gangliosidosis, showing behavioral disturbances, bumping into objects and pronounced ataxia, among other symptoms (Rickmeyer et al., 2013), and in Netherland Dwarf rabbits infected with Enzephalitozoon cuniculi , showing inter alia ataxia (Doboși et al., 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Recent WGS studies in domestic cats have implicated causal variants in novel genes, including KIF3B variants causing retinal degeneration ( OMIA 002267-9685 ), UGDH causing disproportionate dwarfism ( OMIA 000187-9685 ), and GDF7 associated with another brain dysmorphology ( OMIA 000478-9685 ), all diseases with undiagnosed human patients [ 11 13 ]. New models for neuronal ceroid lipofuscinosis ( OMIA 001962-9685 ; OMIA 001443-9685 ) have further utilized WGS and now WES in domestic cats [ 14 , 15 ]. Intergenic structural variation (SV) and genome organization variation are becoming more recognized as keys to gene function.…”
mentioning
confidence: 99%